α;-Glucan Phosphorylase: A Useful Catalyst for Precision Enzymatic Synthesis of Oligo- and Polysaccharides - Kadokawa, Jun-ichi (Current Organic Chemistry, 2017)
Oligo- and polysaccharides have complicated structures because of the structurally different monosaccharide units and differences in stereo- and regioarrangements of glycosidic bonds. As enzymatic reactions proceed in highly regio- and stereo-controlled manner, these are well accepted as a powerful tool for the precise synthesis of well-defined oligo- and polysaccharides. For example, α-glucan phosphorylase has increasingly been identified as the crucial and useful catalyst to provide oligo- and polysaccharide substrates with various structures, which are difficult to synthesize by conventional chemical synthetic approaches. This enzyme catalyzes the polymerization of α-D-glucose 1-phosphate (Glc-1-P) from a maltooligosaccharide primer to produce pure amylose. After the discussion on the principle reaction manner and specificity by α-glucan phosphorylase catalysis, the present review discloses the synthesis of various amylose diblock copolymers by α-glucan phosphorylase-catalyzed enzymatic polymerization using polymeric primers with a maltooligosaccharide moiety at the chain end. The following chemoenzymatic approach including α-glucan phosphorylase-catalyzed enzymatic polymerization is also disclosed. When bio-related polymeric primers with multiple maltooligosaccharide chains are used for enzymatic polymerization, amylose-grafted bio-related polymers, e.g., amylose-grafted polysaccharides and polypeptides, are produced. Based on the fact that α-glucan phosphorylase exhibits weak specificity for substrate recognition, the next section deals with the synthesis of non-natural oligo- and polysaccharides by α-glucan phosphorylase-catalyzed glycosylation using analog substrates of Glc-1-P, which have monosaccharide residues different from Glc. The last section describes the preparation of amylose inclusion supramolecules with polymeric guests from α-glucan phosphorylase- catalyzed enzymatic polymerization in the presence of guest polymers. This polymerization system has been referred to as “vine-twining polymerization.”
Keywords: α-glucan phosphorylase